Pluralidade cultural: limiters e possibilidades na prática pedagógica - Lima, Eliane Brito de (2007)
Interest in the problems concerning the relationships between cultural diversity and school life is increasing in academic circles as a special theme within the search for a truly democratic school. The aim of this work was to analyze pedagogical practices of elementary school teachers, verifying how cultural plurality is treated in the classrooms of municipal schools of Campina Grande, Paraíba, Northeastern Brazil. The analysis initially focused on different conceptions of multiculturalism and interculturalism, as well as on the proposal of the cross-curricular theme Cultural Plurality, which is part of the national curriculum for elementary grades, emergent within the educational policy framework of the 1990s. A qualitative multicase study of two schools was carried, with data collection from the observation of four classrooms, two in each of the selected schools, focusing on teachers pedagogical practices. A pedagogical work dynamic that varied between postures, practices and discourses of cultural homogenization and attempts to contemplate the diversity present in the classroom was verified. Overall, the research evidenced pedagogical practices that favored the construction of a multi/intercultural critical education based on a dialogical and difference inclusive perspective, as well as challenges that still need to be overcome.